The Interpersonal Management and Conflict Management to Improve Journalist Performance (Phenemonology Study at PT WS Media Office) - Retnowati, Wulan; Satibi , Muhammad (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to determine interpersonal conflicts and conflict management that occur in the PT WS media office and to determine the factors that cause them and how to overcome them. The design of this study uses a qualitative approach. The research data collection method used is a deep interview by conducting interviews with leaders and journalists and staff at the PT WS Media Office totaling 5 people. The results of the study indicate that the conflict that occurred was due to personal conflict and interpersonal conflict and conflict of interest. And the PT WS Media Office implemented a conflict management strategy